Electroforming of Fe:STO samples for resistive switching made visible by electrocoloration observed by high resolution optical microscopy. Issue 1691 (10th June 2014) - Havel, Viktor; Marchewka, Astrid; Menzel, Stephan; Hoffmann-Eifert, Susanne; Roth, Georg; Waser, Rainer
ABSTRACT: Resistively switching devices have attracted great attention for potential use in future nonvolatile information storage. Among various oxide materials that show resistive switching (RS) behavior, SrTiO3 (STO) is regarded as a model material to study the effect of valence changes accompanying RS in the oxide [1]. In this class of materials, the RS effect is attributed to rely on the migration of oxygen vacancies and an associated valence change in the cation sublattice. To achieve a switchable state, an initial electroforming step is typically required, which is believed to create conductive regions in the insulating material [2]. Under high electrical stress, an oxygen-deficient region, often referred to as the virtual cathode (VC), is formed [3]. The RS occurs across a very short distance between the VC and the anode, allowing for very short switching times. As the electroforming step greatly impacts the device performance and switching variability, its understanding is essential for device optimization. Electroforming is affected by multiple parameters, e.g. voltage, current, temperature, dopant and defect concentrations, ambient gas atmosphere and time. Distinguishing the influence of the particular parameters is a desirable aim and challenging task. Electrocoloration of Fe-doped STO single crystals has proven a valuable means to visualize valence changes of the Fe ions and is thus suitable to study the formation of the VC. Therefore, we performed electrocoloration experiments and used high resolution transmission light optical microscopy to make the redoxprocesses during electroforming visible. The influence of process driving parameters on the evolution of the VC region is studied. The evolution of the VC is interpreted by drift-diffusion simulation of the time evolution of the oxygen vacancy distribution.